Rectus sheath block for laparoscopic appendicectomy: a randomized clinical trial. Issue 12 (12th January 2015) - Hamill, James K.; Liley, Andrew; Hill, Andrew G.
Abstract: Background: The rectus sheath block is effective in elective paediatric operations, but has not been previously studied in acute laparoscopic surgery. We investigated its effect on pain after laparoscopic appendicectomy for acute appendicitis. Methods: Children aged 8–14 years admitted to a paediatric teaching hospital participated in a randomized clinical trial comparing a rectus sheath block using bupivacaine plus adrenaline with saline control. The primary outcomes were pain scores and opiate use, and secondary outcomes were time in the post‐anaesthetic care unit, duration of hospitalization and recovery. Results: Children in the nerve block group reported significantly reduced global pain scores compared with controls in the first 3 h after surgery, estimated mean 2.22 versus 3.94, effect size −1.80 ( P  = .008). Pain scores after 3 h did not differ between the groups. The groups did not differ in opiate requirements, length of hospital stay or recovery after discharge. Conclusions: In children undergoing acute laparoscopic appendicectomy, a rectus sheath block reduced early post‐operative pain, and could contribute to a multimodal recovery programme.